Diagnóstico del sector camaronero en el cantón El Guabo 2013 - Arévalo Talledo, Nelson Aldemar (2014)
This work was conducted in the southern part of Ecuador, El Oro Province, specifically in Canton El Guabo, considering the next target. 1. Diagnose the current situation in which the shrimp sector of El Canton El Guabo is located. The study group went to 23 shrimp farms in the area, for which the list given by the Secretary of Aquaculture was taken. For the process of survey descriptive tables, figures, summaries of one or more variables under study, which are detailed, averages and percentages were performed. The analysis of the variables of the macro and micro factors, allowed knowing the real situation in the shrimp sector is. Determined the main limiting aspect for shrimp farming was the financing. Shrimp producers agree to a considerable extent, three aspects to further improve the economics of the sector are: Support giving credit and input subsidies government because most are financed by own resources, investing in modernization projects, control and security shrimp sector. The real situation of the shrimp sector despite certain aspects today is better, yields have increased due the full utilization of the productive area, increase the price of shrimp, considered complementary product and human capital used, make this product remains in competitiveness in international markets.